Esophageal Motility Patterns After Peroral Endoscopic Myotomy in Patients With Achalasia - Vackova, Zuzana; Mares, Jan; Krajciova, Jana; Rabekova, Zuzana; Zdrhova, Lucie; Loudova, Pavla; Spicak, Julius; Stirand, Petr; Hucl, Tomas; Martinek, Jan (Journal of neurogastroenterology and motility, 2021)
BACKGROUND/AIMS: Several studies have reported partial recovery of peristalsis in patients with achalasia after myotomy. The aim of our study is to analyze esophageal motility patterns after peroral endoscopic myotomy (POEM) and to assess the potential predictors and clinical impact of peristaltic recovery. METHODS: We performed a retrospective analysis of prospectively collected data of consecutive patients with achalasia undergoing POEM at a tertiary center. High-resolution manometry (HRM) studies prior to and after POEM were reviewed and the Chicago classification was applied. RESULTS: A total of 237 patients were analyzed. The initial HRM diagnoses were achalasia type I, 42 (17.7%); type II, 173 (73.0%); and type III, 22 (9.3%). Before POEM, peristaltic fragments were present in 23 (9.7%) patients. After POEM the Chicago classification diagnoses were: 112 absent contractility, 42 type I achalasia, 15 type II, 11 type III, 26 ineffective esophageal motility, 18 esophagogastric junction outflow obstruction, 10 fragmented peristalsis, and 3 distal esophageal spasm. Altogether 68 patients (28.7%) had signs of contractile activity, but the contractions newly appeared in 47 patients (47/214, 22.0%). Type II achalasia showed a trend for appearance of contractions (P = 0.097). Logistic regression analysis did not identify any predictors of peristaltic recovery. The post-POEM Eckardt score did not differ between patients with and without contractions nor did the parameters of timed barium esophagogram. CONCLUSIONS: More than 20% of achalasia patients have signs of partial recovery of esophageal peristalsis after POEM. It occurs predominantly in type II achalasia but the clinical relevance seems to be negligible.
Keywords: Peristalsis; Myotomy; Esophageal achalasia; Manometry